(3LhGgQ GdaQGFVs
(3ChdgG (B:s
(3EPG eGJ GdEfSGf ChdkG jHOC GdJQcI HJcajfg hJLgjRg Ke JbVi Ojhfg eSCdI QLd eGJ hJQc CHkG dGZjQ , aGdeGd cdg ddCH s
(3BNQgG (B:s
(3eSCdI (B: (3QLd eGJ hJQc RhLGJ hCekG , addRhLGJ GdQHY , hddCe GdKdK , hGdHGbi ddYUHI ef EKfi YTQ JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ cdeI eSCdI HGdMeQIs
(3ef cJH YHO GdbGOQ Rjfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdabg GdESdGejs